(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article examines the critical role of executive personnel in personnel management and evaluates their activities within this framework. It highlights the methodologies used for evaluation, discusses the findings, and provides insights into improving executive effectiveness in managing human resources.